1991
DOI: 10.1111/j.1754-4505.1991.tb01732.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience, periodontal treatment needs, salivary pH, and Streptococcus mutans counts in a preadolescent Down syndrome population

Abstract: The prevalence of dental caries and periodontal treatment needs in an institutionalized population with Down syndrome was examined and the relationship between caries prevalence, salivary pH, and salivary levels of Streptococcus mutans was studied. Thirty-two children with Down syndrome, aged 8 to 13, were compared with two control groups of similar age ranges: healthy children and non-Down mentally retarded (MR) children living in the same institution as the Down syndrome population. The gender ratio mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
2
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 26 publications
5
82
2
7
Order By: Relevance
“…Various studies have demonstrated a correlation between high prevalence of caries and the presence of mutans in the oral cavity of individuals with this syndrome [5,6,8]. Although more than half (60.0%) of the participants in this study showed an elevated number of CFU/mL for mutans streptococci, this finding did not appear to influence the caries index of the individuals in question, since there was no correlation between the number of colonies and the caries index observed.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Various studies have demonstrated a correlation between high prevalence of caries and the presence of mutans in the oral cavity of individuals with this syndrome [5,6,8]. Although more than half (60.0%) of the participants in this study showed an elevated number of CFU/mL for mutans streptococci, this finding did not appear to influence the caries index of the individuals in question, since there was no correlation between the number of colonies and the caries index observed.…”
Section: Discussioncontrasting
confidence: 63%
“…Various investigations have pointed to the existence of variations in the ecosystem of the oral cavity among individuals with Down syndrome, which can lead to physiological alterations in the flow and composition of saliva that are important in the microbial colonization of tooth surfaces by such species as S. mutans and S. sobrinus, interfering directly with the initiation of pathological processes such as dental caries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that caries incidence is reduced in children and young adults with DS (84% caries free 80 ) in comparison with healthy subjects or controls with mental retardation [80][81][82] , although differences may reduce in the permanent dentition 83 . An extensive search of the literature failed to reveal caries data for the adult population over 30 years of age.…”
Section: Cariesmentioning
confidence: 99%
“…It is noteworthy that more recent studies [13,14,20,21] have found that the severity of periodontal disease in individuals with Down syndrome is now milder as compared with that described in older studies [2,[22][23][24]. This fact is likely attributable to better dental care for these individuals, both at home and the dental office, as compared with the past.…”
Section: Prevalence Of Periodontitis In Down Syndromementioning
confidence: 78%